2022
DOI: 10.3390/bs12060180
|View full text |Cite
|
Sign up to set email alerts
|

Chewing Revenge or Becoming Socially Desirable? Anger Rumination in Refugees and Immigrants Experiencing Racial Hostility: Latin-Americans in Spain

Abstract: This paper explores how real scenarios of racial hostility and discrimination trigger anger rumination tendencies in refugees, asylum seekers and immigrants (hereafter RASI). Undergoing discrimination often leads to the development of negative thoughts and behaviors, and to a loss of meaning and self-worth. This could make young RASI particularly vulnerable to being recruited and exploited by extremist groups as they search for identity. We developed a picture-elicitation instrument (the PEI) to provide profes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…However, sample size standards in qualitative research are linked to historical and cultural factors related to the target sample (Marshall et al, 2013 ). The second limitation is the use of the semi-structured interview, even in the presence of a cultural mediator, that could generate social desirability bias in refugee samples (Da Silva Rebelo et al, 2022 ).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…However, sample size standards in qualitative research are linked to historical and cultural factors related to the target sample (Marshall et al, 2013 ). The second limitation is the use of the semi-structured interview, even in the presence of a cultural mediator, that could generate social desirability bias in refugee samples (Da Silva Rebelo et al, 2022 ).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…To this end, a recent systematic review suggested that rumination may be mitigated in response to a potentially traumatic experience through targeting underlying cognitive themes such as anger, guilt, or shame—which are common in ruminative thinking associated with traumatic stress (Moulds et al, 2020). These themes may also apply to racism-related rumination, but others such as despair and social desirability have also been identified as maladaptive ruminative responses (da Silva Rebelo et al, 2022). Thus, clinicians should assess specific emotional and cognitive responses to racial discrimination among their youth clients and assist them in labeling and processing those responses.…”
Section: Discussionmentioning
confidence: 99%
“…In 2020, and despite the mobility restrictions taken due to the COVID-19 pandemic, half a million people settled in Spain, and in 2022, 478,990 foreigners chose Spain as their destination to live (INE, 2022) almost. In this regard, different studies carried out in the Spanish context (Urbanos-Garrido, 2016;Rinken, 2019) have shown that immigrants are the population group most affected by prejudice and discrimination (Plaza del Pino, 2012;Álvarez-Castillo et al, 2016;Cala et al, 2018;da Silva Rebelo et al, 2022). Other studies on interculturality also highlight the relevance of intercultural training (Cernadas Ríos et al, 2014;Nishida et al, 2019), as a mechanism for raising awareness and reducing or eliminating prejudice toward people with different backgrounds and cultures (Albalá Genol et al, 2020;Velasco, 2020).…”
Section: Introductionmentioning
confidence: 99%